Safe to sleep: Community‐based caregiver training. Issue 4 (28th September 2020) - Vladescu, Jason C.; Day‐Watkins, Jessica; Schnell, Lauren K.; Carrow, Jacqueline N.
Abstract : Annually, thousands of infant deaths are classified as sudden unexpected infant deaths (SUIDs). In an effort to reduce the risk of SUIDs, the American Academy of Pediatrics has made a number of recommendations to educate caregivers, childcare providers, and healthcare professionals on safe infant sleep practices. The purpose of the current study was to extend the literature on safe infant sleep practices by teaching caregivers to arrange safe infant sleep environments using a mannequin and common infant items. We partnered with community‐based agencies to evaluate the effectiveness of behavioral skills training delivered in a single training session as part of the ongoing pre‐ or postnatal care these agencies provided. Following training, all participants demonstrated a substantial change in responding and returned favorable social validity ratings. We discuss these outcomes in light of previous studies, limitations, and future directions.